Food grown on fire stations as a potential pathway for firefighters' exposure to per- and poly-fluoroalkyl substances (PFAS). (October 2022) - Mesfin Tefera, Yonatal; Gaskin, Sharyn; Mitchell, Krystle; Springer, David; Mills, Simon; Pisaniello, Dino
Graphical abstract: Highlights: PFAS were measured in foods, water, dust, soil, and appliances on fire stations. Multiple pathways for firefighters' exposure to PFAS were characterised. PFAS Intake levels were estimated under different exposure scenarios. Consumption of food grown on fire stations seems the dominant exposure pathway. Abstract: Human exposure to per- and polyfluoroalkyl substances also known as PFAS is an ongoing occupational and environmental health problem. This study seeks to characterise multiple pathways for firefighters' exposure to PFAS. PFAS were analysed in 688 environmental samples such as eggs, fruits, vegetables, dust, soil, surface swabs, appliance washes and water obtained from fire stations. Relevant exposure pathways were identified and daily intake levels were estimated using PFAS concentrations and exposure factors relevant to firefighters. Five PFAS including perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA), perfluorohexane sulfonic acid (PFHxS), 6:2 fluorotelomer sulfonate (6:2 FTS), and 8:2 fluorotelomer sulfonic acid (8:2 FTS) were frequently detected in the samples. Based on the median concentrations in each sample type, PFOS was the most abundant contaminant in eggs (80%), fruits (52%), dust (81%), surface swab (66%), soil (83%) and appliance wash (31%) samples. On the other hand, PFHxS was most abundant in vegetables (77%) and 8:2 FTS in water (58%). The intake estimation results show that dietary exposure from ingestion of foods produced on fire stations was the predominant exposure pathway, representing 82% and 62% of firefighters' total PFAS intake under typical and worst-case exposure scenarios, respectively. Incidental ingestion and dermal absorption of PFAS in dust contributed 15% for typical and 34% for worst-case exposure scenarios. The relative contributions from incidental ingestion and dermal absorption of PFAS in soil and appliance washes were insignificant. Overall, the study identifies multiple exposure pathways relevant to career firefighters including consumption of food grown on fire stations, which has not previously been recognised within the occupational exposure context. The results suggest exposure control strategies that target foods produced on fire stations could substantially reduce firefighters' exposure to PFAS.